Tinjauan Kritis Terhadap Peraturan Mahkamah Agung Nomor 2 Tahun 2012 Tentang Batasan Tindak Pidana Ringan dan Jumlah Denda dalam KUHP - Tahir, Ach (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2012)
Justice is one of the purposes of any legal system, even the most important is mygoal. There are still other legal purposes is also always the purpose of the law, namelyjustice, rule of law, expediency, and order. However, from the fourth grade, according tothe Greek philosopher, Plato, justice is the highest virtue. According to Plato justice is"Justice is the supreme virtue roomates Harmonize all other virtues." However, theSupreme Court Regulation No. 2 Year 2012 About Limits Lightweight CrimePenalties in the Criminal Code and the amount still falls short of justice as a whole.PERMA No.2/2012 only protect the suspect, not protecting the victim if the limit isonly a nominal loss of USD 2.5 million, but it should not be detained suspects andvictims should not be an appeal. Rp 2.5 million in Jakarta probably not worth much.But in the area, the number is very large. However, with the Supreme Court No.2/2012, the victim can not do much because the case was only a minor criminaloffense.